Interaction between hydrogenase maturation factors HypA and HypB is required for [NiFe]-hydrogenase maturation. - Kwok-Ho Chan; Ka-Man Lee; Kam-Bo Wong (PLoS ONE, 2012)
The active site of [NiFe]-hydrogenase contains nickel and iron coordinated by cysteine residues, cyanide and carbon monoxide. Metal chaperone proteins HypA and HypB are required for the nickel insertion step of [NiFe]-hydrogenase maturation. How HypA and HypB work together to deliver nickel to the catalytic core remains elusive. Here we demonstrated that HypA and HypB from Archaeoglobus fulgidus form 1:1 heterodimer in solution and HypA does not interact with HypB dimer preloaded with GMPPNP and Ni. Based on the crystal structure of A. fulgidus HypB, mutants were designed to map the HypA binding site on HypB. Our results showed that two conserved residues, Tyr-4 and Leu-6, of A. fulgidus HypB are required for the interaction with HypA. Consistent with this observation, we demonstrated that the corresponding residues, Leu-78 and Val-80, located at the N-terminus of the GTPase domain of Escherichia coli HypB were required for HypA/HypB interaction. We further showed that L78A and V80A mutants of HypB failed to reactivate hydrogenase in an E. coli ΔhypB strain. Our results suggest that the formation of the HypA/HypB complex is essential to the maturation process of hydrogenase. The HypA binding site is in proximity to the metal binding site of HypB, suggesting that the HypA/HypB interaction may facilitate nickel transfer between the two proteins.